FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT SUKUK (STUDI EMPIRIS PERUSAHAAN YANG DIPERINGKAT FITCH RATING) - RIFQI MUHAMMAD; CAHYANINGTYAS TIRZA SILVIANI BIYANTORO (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2019)
This study aims to determine the effect of profitability, leverage, firm size, and growth of the company to the sukuk ratings. The main purpose of this rating is to provide information to investors about the state of sukuk issuers and what risks will be borne, so that can be used as consideration of investors in investing. The sample in this research is sukuk issuer company rated by rating agency Fitch Rating period 2013-2016. Samples were chosen using purposive sampling method and 15 companies were selected. Data analysis was done by multiple linear regression model and using SPSS 22.0 software. The results of this study indicate that the profitability and firm size have a positive and significant impact on the rating of sukuk. Leverage has a negative and significant impact on the sukuk rating. While the growth of the company has a positive effect is not significant on the rating of sukuk.